Features of Intracellular Matrix State during Development and Formation of COPD Clinical Phenotypes - T. V. Tayutina; S. V. Shlyk; D. A. Kudlay; S. V. Smerdin; L. A. Shovkun; E. A. Kizhevatova; N. Yu. Nikolenko; E. D. Kampos (Туберкулез и болезни лёгких, 2024)
The objective: to evaluate state of extracellular matrix markers and their tissue inhibitors during development and formation of clinical phenotypes of COPD, in patients facing the high risk of developing exacerbations.Subjects and Methods. 96 COPD patients (73% men and 27% women) were examined. Patients were randomized into the following groups: Group 1 included 40 COPD patients with bronchitis phenotype; Group 2 included 38 patients with emphysema phenotype; and Control Group consisted of 18 practically healthy subjects. All patients underwent a comprehensive clinical and laboratory examination. Levels of matrix metalloproteinases (total MMP-9 and MMP-2) and their tissue inhibitors TIMMP1 and TIMMP2 were determined by ELISA.Results. The development of COPD, regardless of the clinical phenotype of the disease, is accompanied by pronounced expression of extracellular matrix markers MMP-9 and MMP-2. Regardless of the COPD clinical phenotype, elevated activity of metalloproteinases is accompanied by inhibition of production of TIMMP2 and dysfunction of the MMP-9/TIMMP1 antiprotease system. In COPD patients with MMP-2 level of 214 ng/ml, the formation of bronchitis phenotype can be predicted, while with MMP-2 level of 214 ng/ml or more, the formation of emphysema phenotype can be predicted.